2017
DOI: 10.1371/journal.pone.0174152
|View full text |Cite
|
Sign up to set email alerts
|

Differential recruitment efficacy of patient-derived amyloidogenic and myeloma light chain proteins by synthetic fibrils—A metric for predicting amyloid propensity

Abstract: BackgroundMonoclonal free light chain (LC) proteins are present in the circulation of patients with immunoproliferative disorders such as light chain (AL) amyloidosis and multiple myeloma (MM). Light chain-associated amyloid is a complex pathology composed of proteinaceous fibrils and extracellular matrix proteins found in all patients with AL and in ~10–30% of patients who presented with MM. Amyloid deposits systemically in multiple organs and tissues leading to dysfunction and ultimately death. The overall s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…AL1κ and MM2λ are the proteins that presented similar rate constants of recruitment into amyloid fibrils in our previous study on recruitment of light chains [19]. However, their %LC bound to fibrils is dramatically different.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…AL1κ and MM2λ are the proteins that presented similar rate constants of recruitment into amyloid fibrils in our previous study on recruitment of light chains [19]. However, their %LC bound to fibrils is dramatically different.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, the modulating effect of the constant domain, and host factors may play important role in amyloid aggregation. Previously, we have reported that both MM and AL BJPs were recruited by amyloid-like V L fibrils; however the extent of recruitment of AL-derived BJPs was significantly greater, allowing discrimination of the two disease populations [19]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations